Nox Emissions Dependencies on Gas Recycling in A 132 mw Steam Boiler - Quintero, Guillermo Alfredo Mosquera; Recio, Ángel Amado Recio; Gordín, Reinaldo Javier Guillén; Alegría, Wilar Alberto Villacreses (Journal of Posthumanism, 2025)
This paper presents the calculation of the concentration of nitrogen oxides (NOx) in the furnace of a 132 MW steam generator located at the CELEC EP THERMOELECTRIC PLANT TERMOESMERALDAS BUSINESS UNIT in the Republic of Ecuador. This steam generator is equipped with two levels of tangential burners located at each corner of the furnace, which burn type 6 fuel oil tangentially in a vertical whirlwind. A verification thermal calculation method has been developed for the furnaces of the steam generators, from which the concentration of NOx has been determined at different operating load levels (100%, 75% and 50%) with different percentages of gas recirculation (0%, 10% and 20%), maintaining a fixed coefficient of excess air of 5%. This calculation was performed using Excel, which allowed the identification of operating conditions that could reduce NOx formation while maintaining adequate thermal efficiency.